Moisture damage assessment using surface energy, bitumen stripping and the SATS moisture conditioning procedure - Grenfell, James; Apeagyei, Alex K.; Airey, Gordon (Taylor & Francis, 2015)
Durability is one of the most important properties of an asphalt mixture. A key factor affecting the durability of asphalt pavements is moisture damage. Moisture damage generally results in the loss of strength of the mixture due to two main mechanisms; the loss of adhesion between bitumen and aggregate and the loss of cohesion within the mixture. Conventional test methods for evaluating moisture damage include tests conducted on loose bitumen-coated aggregates and those conducted on compacted asphalt mixtures. The former test methods are simpler and less expensive to conduct but are qualitative/subjective in nature and do not consider cohesive failure while the latter, though more quantitative, are based on bulky mechanical test set-ups and therefore require expensive equipment. Both test methods are, however, empirical in nature thus requiring extensive experience to interpret/use their results. The rolling bottle test (RBT) (EN 12697-11) for loose aggregate mixtures and the saturation ageing tensile stiffness (SATS) test (EN 12697-45) for compacted asphalt mixtures are two such methods, which experience suggests, could clearly discriminate between ‘good’ and ‘poor’ performing mixtures in the laboratory. A more fundamental approach based on surface energy (SE) measurements offers promise to better understand moisture damage. This article looks at results from the rolling bottle and the SATS tests in an attempt to better understand the underlying processes and mechanisms of moisture damage with the help of SE measurements on the constituent bitumen and aggregates. For this work, a set of bitumens and typical acidic and basic aggregate types (granite and limestone) were selected. Combinations of these materials were assessed using both the rolling bottle and SATS tests. The SE properties of the binders were measured using a dynamic contact angle Analyser and those of the aggregates using a dynamic vapour sorption device. From these SE measurements it was possible to predict the relative performance of both the simple RBT and the more complicated SATS test. Mineralogical composition of the aggregates determined using a mineral liberation analyser was used to explain the differences in performance of the mixtures considered.